Rancang Bangun Aplikasi Pembelajaran IPA Berbasis Multimedia Pada Sekolah Dasar - Merry Sul; Nur Wahidin Ashari (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The quality of learning is an important factor in improving student achievement. Currently, not all students can understand and apply the material taught in class because the lessons are abstract, while what is needed are real objects for learning materials. One of the learning media that can be developed at this time is learning applications. Application-based learning media is easy to access and use for everyone, and can be done anywhere, at home or on the move, allowing users to learn on their own time. The type of research used is Research and Development (R&D). The system development method used in this study is the Waterfall model. The media developed above has gone through the validation stage. The results of the validation state that the resulting learning media is suitable for use by school students. The developed application has interesting features such as attractive images, animations. In addition, the application also displays interesting visual material. To evaluate student understanding, this application is also equipped with a quiz.